Networked Learning Reflections and Challenges (Research in Networked Learning,, 2018)
The book is based on nine selected, peer-reviewed papers presented at the 10th biennial Networked Learning Conference (NLC) 2016 held in Lancaster. Informed by suggestions from delegates, the nine papers have been chosen by the editors (who were the Chairs of the Conference) as exemplars of cutting edge research on networked learning. Further reviews of all papers were conducted once they were revised as chapters for the book. The chapters are organized into two sections: 1) Situating Networked Learning: Looking Back - Moving Forward, 2) New Challenges: Designs for Networked Learning in the Public Arena. Further, we include an introduction which looks at the evolution of trends in Networked Learning through a semantic analysis of conference papers from the 10 conferences. A final chapter draws out perspectives from the chapters and discusses emerging issues. The book is the fifth in the Networked Learning Conference Series. .